Determinants of International (Interethnic) Conflicts in the Russian Federation Regions - V N Ivanov (Vestnik Rossijskogo universiteta družby narodov. Seriâ Sociologiâ, 2012)
The events of the past few years in Moscow and in a number of regions of the Russian Federation are evidence of the growing tension in international (interethnic) relations. In this sphere, sociological studies can play an important role by promptly revealing the arising contradictions and problems. This article deals with the results of these studies and their importance for preventing international (interethnic) conflicts.